Mais vídeos, menos textos”: ensino e aprendizagem em História e produções audiovisuais - SILVA, Anderson Rodrigo Tavares (Universidade Federal do Pará, 2019)
This dissertation has as main objective to analyse questions about the use and production of audiovisuals sources and conducting research activities on the historical concept of the Brazilian military regime through a participant research carried out with a group of high school students of the public school Acy de Barros. The main problem was to identify which elements of their culture the graduating high school students turn to when they are learning history. Based on this, the classroom-workshop method was used, according to the perspective of Isabel Barca (2004), with the purpose of stimulating the learning of history through the use and production of historical sources using cellphones (smartphones) as a didactic resource. As a culminating activity of this teaching-learning process in history, students built short film audiovisual products in different formats on themes related to the historical concept military regime.